Epidemiology and outcomes of pregnancy and obstetric complications in trauma in the United Kingdom. Issue 1 (January 2016) - Battaloglu, Emir; McDonnell, Declan; Chu, Justin; Lecky, Fiona; Porter, Sir Keith
Abstract: Objective: To understand the epidemiology of pregnancy and obstetric complications encountered in the management of pregnant trauma patients. Methods and design: Retrospective analysis of national trauma registry for recording of pregnancy status or obstetric complication in cases of trauma. Sub-division of patient cohort by severity of trauma and stage of pregnancy. Comparison of data sets between pregnant trauma patients and age-matched non-pregnant female trauma patients to determine patterns of injury and impact upon clinical outcomes. Settings: National registry data for the United Kingdom. Outcome: For the five year period between 2009 and 2014, a total of 15, 140 female patients, aged between 15 years old and 50 years old were identified within the trauma registry. A record of pregnancy was identified in 173 patients (1.14%) from within this cohort. Mechanisms of injury within the cohort of pregnant trauma patients saw increased rate of vehicular collision and interpersonal violence, especially penetrating trauma. Higher abbreviated injury scores were recorded for the abdominal region in pregnancy than in the non-pregnant cohort. Maternal mortality rates were seen to be higher, when compared with the non-pregnant trauma patient. Foetal survival rate from this series was 56% following trauma. Foetal death in pregnant trauma patients most frequently occurred in the 2nd trimester. No cases of isolated foetal survival were recorded following maternal trauma. Conclusions: Trauma to pregnant patients is rare in the United Kingdom, encountered in 1% of female trauma patients of child bearing age. Observations in altered mechanisms of injury and clinical outcomes were recorded. This provides useful information regarding the clinical management of pregnant trauma patients and offers potential areas to investigate to optimise their care, as well as to focus injury prevention measures. Level of evidence: IV—Case series.